Evaluación de la adición de nutrientes (melaza de caña y nutriente comercial) para el crecimiento de levaduras en la elaboración de vino de naranjilla (Solanum quitoense Lam) - Artos Uribe, Katherine Dayana (2022)
This project aimed to evaluate nutrients two types incorporation (cane molasses and commercial nutrient) for yeasts growth (Saccharomyces cerevisiae) naranjilla wine (Solanum quitoense Lam) production. A completely random block design was applied on factorial arrangement of 23 with a total of 8 treatments with two repetitions. Three study factors were determined; factor A (maturity index), factor B (type of nutrient) and factor C (yeast concentration). The results of the present research regarding physicochemical parameters such as (SST, pH and °GL) collected from fermentation process, were entered into Infostat statistical program, in which it was established that treatment t3 (grade 3 - cane molasses - 1 g/L of yeast) is the best treatment because the conversion of soluble solids to alcoholic degrees was more efficient during the fermentation. In addition, an order and frequency design was carried out for the sensory analysis of the 16 treatments after the wine fermentation process, establishing that the t3 treatment obtained a higher acceptability of its organoleptic characteristics. Next, a microbiological analysis was carried out using growth curves to the best treatment t3, the results were expressed in CFU/ml and UP, where an exponential growth of yeasts on fermentation process is evident. Finally, a physical-chemical and microbiological analysis was carried out in an external laboratory to the best treatment t3 presenting the following results: °GL (11.0), AT (7.77 g/L), AV (0.21 g/L), ASL (93.70 mg/L), M (<0.01 mg/0.1L), AT (5.93%), Salmonella ssp (absent), Molds (<10 CFU/ml), Yeasts (1.5x104 CFU/ml), complying with established parameters at NTE INEN 374 (Physical-chemical requirements for alcoholic beverages. Fruit wine) and NTE INEN 2802 (Microbiological requirements for alcoholic beverages. Cocktails or mixed alcoholic beverages and aperitifs) except for the amount of yeast.